Cost‐effectiveness of generic pan‐genotypic sofosbuvir/velpatasvir versus genotype‐dependent direct‐acting antivirals for hepatitis C treatment. Issue 12 (25th June 2018) - Goel, Amit; Chen, Qiushi; Chhatwal, Jagpreet; Aggarwal, Rakesh
Abstract: Background and Aim: Treatment of hepatitis C virus (HCV) infection with low‐cost generic direct‐acting antivirals (DAAs) available in India and other developing countries needs determination of HCV genotype ("genotype‐dependent" regimens). Generic velpatasvir, a DAA that obviates the need for genotype determination ("pan‐genotypic" regimen), recently became available but is costlier. The aim of this study was to evaluate the cost‐effectiveness of genotype‐dependent versus pan‐genotypic DAA treatments in India. Methods: A previously validated microsimulation model, adapted to Indian population, was used to compare the costs and long‐term outcomes of three scenarios: no treatment, treatment with genotype‐dependent regimens, and treatment with pan‐genotypic regimen. Input parameters were derived from literature. Using a payer's perspective and lifetime time horizon, quality‐adjusted life‐years (QALYs), total costs, and incremental cost‐effectiveness ratio were calculated. Both deterministic and probabilistic sensitivity analyses were also conducted. Results: At the current price ($US223 for 4 weeks), pan‐genotypic regimen was cost‐saving compared with no treatment. Compared with genotype‐dependent regimens, it increased QALYs by 0.92 and increased costs by $US107 but was deemed cost‐effective with an incremental cost‐effectiveness ratio of $US242 per QALY gained. Probabilistic sensitivity analysis also supported the cost‐effectiveness of pan‐genotypic regimen. At the reduced price of $US188 for 4 weeks, the pan‐genotypic regimen will become cost‐neutral to genotype‐dependent regimens (current price: $US100 for 4 weeks). Conclusions: At current prices, velpatasvir‐based pan‐genotypic regimen is cost‐effective for HCV treatment in India where generic drugs are available. A reduction in the prices of pan‐genotypic regimen has the potential to make its use cost‐saving while simplifying treatment in community‐level programs aimed at HCV elimination.